Natural history of the hyperdominant tree, Pentaclethra macroloba (Willd.) Kuntze, in the Amazon River estuary - A. R. Dantas; C. C. Vasconcelos; M. C. Guedes; A. C. Lira-Guedes; M. T. F. Piedade (Brazilian Journal of Biology)
Abstract Pentaclethra macroloba is a hyperdominant species with multiple uses in the Amazon. This species tolerates varying flood amplitudes, however the effect of flood topographic gradient on its ecophysiology remains unclear. We want to know if individuals from the high (10 trees) and low (20 trees) várzea show distinct phenological patterns as a function of the flood gradient, as well as their colonization strategies and their seed predators. From February 2018 to December 2019, we monitored the phenology of P. macroloba. There was no difference in phenological patterns between the two environments, but flooding caused different phenological responses. The increase in temperature favored the production of flower buds and increased precipitation reduced the proportion of flowering trees in both environments. The increase in rainfall and river flood level favored the ripe fruit only in the low várzea where individuals were most exposed to flooding. When the flood level increased, there was a greater proportion of trees losing leaves in both environments. The species produces high variability in seed size (length: H = 49.2, p > 0.001; width: H = 62.5, p > 0.001; weight: H = 70.4, p > 0.001). The seed predation rate was 5%, mainly caused by Carmenta surinamensis moth larva. The flood gradient established different phenological responses in the species, directing trees to have a better reproductive performance. The low predation rate and the variability in seed size are factors that contribute to the formation of large population densities in the Amazon River estuary.